HEALTH SAVING STRATEGY AS A FACTOR OF “SOCIETY WELLNESS” - Когiakovtseva, Olga; Tarkhanova, Irina; Upeniece, Irena; Arnis, Voldemars; Fedorova, Polina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The article deals with the problem of reducing the motor activity of a modern man, especially a young man, in connection with scientific and technological progress. The results of the presented study confirm these fears: inactive lifestyle is becoming the norm. The importance of promoting the health saving strategy as one of the factors of successful social and economic development of the society is justified.